IMPLEMENTASI METODE PEMBELAJARAN KOOPERATIF TIPE SCRAMBLE DALAM MENINGKATKAN KEMAMPUAN BERFIKIR KREATIF PESERTA DIDIK MATA PELAJARAN BAHASA ARAB DI MIN 11 BLITAR: IMPLEMENTASI METODE PEMBELAJARAN KOOPERATIF TIPE SCRAMBLE DALAM MENINGKATKAN KEMAMPUAN BERFIKIR KREATIF PESERTA DIDIK MATA PELAJARAN BAHASA ARAB DI MIN 11 BLITAR - Eli Dwi Nabila, Eli Dwi Nabila; Afthon Ulin Nuha, Muhammad; Widayanti, Rizka; Musyafaah, Nurul; Sabilar Rosyad, Muh; Ni'mah, Mamluatun; Rondi, M.; Dr. Faedurrohman, M.Pd.I (The Elementary Journal, 2025)
Learning methods play a vital role in education by helping teachers deliver material effectively. In today’s context, creative learning methods are essential to make lessons more engaging and meaningful. This study focuses on implementing the scramble-type cooperative learning method, integrated with the traditional game "gederek," to improve students’ creative thinking skills in Arabic language classes at MIN 11 Blitar. The study aims to describe the planning, implementation, and impact of this learning method. Using a qualitative approach, data were collected through interviews, observations, and documentation. The research was driven by the issue of monotonous teaching methods, which often lead to student disengagement. To address this, one Arabic teacher applied the scramble method, involving games and group discussions, where students answered Arabic vocabulary questions in a fun and interactive manner. The implementation aligned with the lesson plan and led to positive outcomes. Students were more active, creative, and engaged in collaborative learning, showing an ability to generate original ideas. In conclusion, the scramble-type cooperative learning method proved highly effective at the Madrasah Ibtidaiyah level. It not only enhanced students’ creative thinking skills but also created a more dynamic and enjoyable learning environment. The method successfully met the indicators of creative thinking.